Plasma concentrations of branched-chain amino acids differ with Holstein genetic strain in pasture-based dairy systems - Ezequiel Jorge-Smeding (Nature Portfolio, 2021)
Abstract In pasture-based systems, there are nutritional and climatic challenges exacerbated across lactation; thus, dairy cows require an enhanced adaptive capacity compared with cows in confined systems. We aimed to evaluate the effect of lactation stage (21 vs. 180 days in milk, DIM) and Holstein genetic strain (North American Holstein, NAH, n = 8; New Zealand Holstein, NZH, n = 8) on metabolic adaptations of grazing dairy cows through plasma metabolomic profiling and its association with classical metabolites. Although 67 metabolites were affected (FDR < 0.05) by DIM, no metabolite was observed to differ between genetic strains while only alanine was affected (FDR = 0.02) by the interaction between genetic strain and DIM. However, complementary tools for time-series analysis (ASCA analysis, MEBA ranking) indicated that alanine and the branched-chain amino acids (BCAA) differed between genetic strains in a lactation-stage dependent manner. Indeed, NZH cows had lower (P-Tukey < 0.05) plasma concentrations of leucine, isoleucine and valine than NAH cows at 21 DIM, probably signaling for greater insulin sensitivity. Metabolic pathway analysis also revealed that, independently of genetic strains, AA metabolism might be structurally involved in homeorhetic changes as 40% (19/46) of metabolic pathways differentially expressed (FDR < 0.05) between 21 and 180 DIM belonged to AA metabolism.